The Role of Ustadzah Pengabdian in Disciplining Intensive Female Students of IDIA Prenduan Academic Year 2023-2024 - Fayruzah El-Faradis; Nepita Sari (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Acts of lack of discipline often occur and they are everywhere, even in educational institutions such as Pesma (Student Islamic Boarding School). There are many mahasantri who live a disciplined life and every year they can improve their Ma'had discipline, but there are still some mahasantri who are not disciplined, such as being late for congregational prayers, being late for big boarding events and not being disciplined when sleeping at night and there are still many acts of lack of discipline by mahasantri that are carried out by mahasantri by several mahasantri. Planning, processing and evaluating learning and various things is one of the competencies that must be mastered by a service ustadzah. The problem raised in this research is what is the role of the service ustadzah in disciplining the intensive female students of IDIA Prenduan in 2023-2024 which is broken down into 2, namely: 1. What is the role of the service ustadzah in disciplining the intensive female students at Ma'had Institut Dirosat Islamiyah Al-Amien Prenduan . 2. What are the supporting and inhibiting factors for service ustadzah in disciplining students at Ma'had Institut Dirosat Islamiyah Al-Amien Prenduan. The data collection in this research used observation, interviews and documentation methods. To test the validity of the data, this research uses source triangulation and technical triangulation with pre-field research stages, field worker stages and data analysis stages. Based on the discussion of the results of this research, it can be concluded that the roles of service ustadzahs in disciplining mahasantri are: Role as caregiver, role as controller/supervisor, role as motivator, role as friend and family and the role of Uswatun Hasanah for intensive female students. The supporting factors for service ustadzah in intensively disciplining female students are: The existence of BEMA administrators, the existence of rules and regulations, the existence of self-awareness of the importance of discipline. There are also factors inhibiting service ustadzah in disciplining intensive female students, namely: Lack of self-awareness of the importance of discipline, using seniors as benchmarks and differences in character.